An injectable in situ lipid phase transition system for sustained delivery of dabigatran etexilate with low burst release. Issue 89 (15th December 2017) - Zhang, Xuanmiao; Hu, Mei; Wei, Guangfei; Jia, Mengdi; Gong, Tao; Liu, Ji
Abstract : The first report of dabigatran exilate sustained release injection that exhibited great potential in controlling initial burst release. Abstract : Controlling initial burst release remains one of the greatest challenges in developing in situ -forming parenteral depot formulations. Here an injectable lipid phase transition system (LPTS) was fabricated to provide sustained release of dabigatran exilate (DABE) with low burst release. LPTS was prepared in a low-viscosity injectable state by simple mixing of sorbitan monooleate and phospholipids with ethanol. After subcutaneous injection, the liquid LPTS underwent a phase transition in situ and formed a semi-solid mesophase, creating a drug-release depot. The physicochemical properties of DABE–LPTS were investigated using rheological techniques. Release profiles in vitro indicated that DABE–LPTS has suitable controlled release properties. Pharmacokinetic studies showed that DABE–LPTS significantly reduced the initial burst release after subcutaneous injection in rats. Pharmacodynamic studies showed that single administration of DABE–LPTS exerted anticoagulant effects in rats lasting 1 week. DABE–LPTS showed good biocompatibility in vitro and in vivo . Thus, the LPTS-based depot system shows promise for sustained DABE delivery with low burst release.